Vladimir Bartol in film - Virk, Tomo (Slavia Centralis, 2025)
Vladimir Bartol and Film. The article deals with Vladimir Bartol’s attitude towards film. Film is present in Bartol’s artistic prose primarily as a means of stereotypically characterising female figures. His unpublished diary entries, however, show a different picture. Here, he compares his works of fiction with various movies, mentioning plans for the filming of his works and revealing his view on the question of why his novel Alamut did not see the planned feature-length film adaptation.